Leonardo Da Vinci His Life and Works in 500 Images - Rosalind Ormiston (London LORENZ BOOKS, 2011)
This comprehensive new book is an essential volume for anyone who wants to learn more about Leonardo and to survey his greatest works in one beautifully illustrated collection. The first part contains a detailed exploration of Leonardo's life. It details his childhood, family life and education, and then explores his interests in architecture, engineering and science as well as his career as a painter. The second part of the book contains a gallery of over 300 of Leonardo's major paintings, drawings and designs. These superb reproductions are accompanied by thorough analysis of each artwork and its significance within the context of his life, his technique and his body of work as a whole.
Keywords: Art & Design -- Art & Design; Artists -- Artists